A nanofabricated plasmonic core–shell-nanoparticle library. Issue 44 (30th October 2019) - Susarrey-Arce, Arturo; Czajkowski, Krzysztof M.; Darmadi, Iwan; Nilsson, Sara; Tanyeli, Irem; Alekseeva, Svetlana; Antosiewicz, Tomasz J.; Langhammer, Christoph
Abstract : Lithographic method of making nanoarchitectures composed of metal core and oxide/nitride shell decorated with nanoparticles with widely different materials. Abstract : Three-layer core–shell-nanoparticle nanoarchitectures exhibit properties not achievable by single-element nanostructures alone and have great potential to enable rationally designed functionality. However, nanofabrication strategies for crafting core–shell-nanoparticle structure arrays on surfaces are widely lacking, despite the potential of basically unlimited material combinations. Here we present a nanofabrication approach that overcomes this limitation. Using it, we produce a library of nanoarchitectures composed of a metal core and an oxide/nitride shell that is decorated with few-nanometer-sized particles with widely different material combinations. This is enabled by resolving a long-standing challenge in this field, namely the ability to grow a shell layer around a nanofabricated core without prior removal of the lithographically patterned mask, and the possibility to subsequently grow smaller metal nanoparticles locally on the shell only in close proximity of the core. Focusing on the application of such nanoarchitectures in plasmonics, we show experimentally and by Finite-Difference Time-Domain (FDTD) simulations that these structures exhibit significant optical absorption enhancement in small metal nanoparticles grown on the few nanometer thin dielectric shell layer around a plasmonic core, and derive design rules to maximize the effect by the tailored combination of the core and shell materials. We predict that these structures will find application in plasmon-mediated catalysis and nanoplasmonic sensing and spectroscopy.